PENGEMBANGAN MODEL PELATIHAN PENINGKATAN KOMPETENSI GURU SD BERBASIS APLIKASI EDMODO - Susari, Erfi Fitri; Nomi, Ahmad Suryadi; Wicaksono, Dirgantara (Universitas Muhammadiyah Jakarta, 2020)
This study aims to measure the benefits of edmodo application, in the Islamic Elementary School of Cikal Harapan I BSD. Teachers are given alternative edmodo applications to be used in the development of training models, as an answer to the problem of how to improve development models in the midst of their busy activities. By using the edmodo application, teachers in the Islamic Elementary School of Cikal Harapan I BSD can improve pedegogical competence through the edmodo application-based training they use. Although everyday teachers are accompanied by modern communication tools such as smartphones, computers and laptops, it is not easy to use new methods. Patience and perseverance are needed to introduce this model development model, especially the introduction of each edmodo application feature, active interaction when given training material as well as their seriousness to improve skills in using the edmodo application. In addition to practicing the use of edmodo applications in 42 teachers, they also gave questionnaires. Data in the field is inputted with the SPSS program which provides an overview of the level of teacher acceptance of the use of the edmodo application. Of the 42 teachers who were the subjects of the study, there were 50 percent who could ultimately benefit from using the Edmodo application. The rest is split in constraints due to time constraints, incompatible devices and difficulty understanding edmodo's application features.